2016
DOI: 10.3389/fnins.2016.00179
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying CLARITY: Quantitative Optimization of the Diffusion Based Delipidation Protocol for Genetically Labeled Tissue

Abstract: Tissue clarification has been recently proposed to allow deep tissue imaging without light scattering. The clarification parameters are somewhat arbitrary and dependent on tissue type, source and dimension: every laboratory has its own protocol, but a quantitative approach to determine the optimum clearing time is still lacking. Since the use of transgenic mouse lines that express fluorescent proteins to visualize specific cell populations is widespread, a quantitative approach to determine the optimum clearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 25 publications
(31 reference statements)
1
27
0
Order By: Relevance
“…FUnGI was effective in clearing mammary tissue in 2 h at room temperature, and tissue transparency was maintained ( Figure 1A). Comparison of FUnGI with the clearing agent Ce3D and glycerol (60% or 80%) revealed that both FUnGI and Ce3D, but not glycerol, could efficiently clear the mammary gland, as verified through quantification using the bulk tissue clarity index (BTCi) (Magliaro et al, 2016) (Figures S1B and S1C). In addition, FUnGI appeared to have a faster and higher clearing capacity than Ce3D.…”
Section: Development Of the Clearing Agent Fungi And Lsr-3d Imaging Pmentioning
confidence: 82%
See 1 more Smart Citation
“…FUnGI was effective in clearing mammary tissue in 2 h at room temperature, and tissue transparency was maintained ( Figure 1A). Comparison of FUnGI with the clearing agent Ce3D and glycerol (60% or 80%) revealed that both FUnGI and Ce3D, but not glycerol, could efficiently clear the mammary gland, as verified through quantification using the bulk tissue clarity index (BTCi) (Magliaro et al, 2016) (Figures S1B and S1C). In addition, FUnGI appeared to have a faster and higher clearing capacity than Ce3D.…”
Section: Development Of the Clearing Agent Fungi And Lsr-3d Imaging Pmentioning
confidence: 82%
“…For tissue clearing assessment and measurement of mammary gland size, images were acquired on a stereomicroscope (Leica M205FA). For tissue clearing assessment, we used the Bulk Tissue Clarification index (Magliaro et al, 2016). For quantification of sample size changes, image thresholding was performed using FIJI and the pixel area was measured.…”
Section: Star+methodsmentioning
confidence: 99%
“…dopaminergic neurons or parva-albuminergic neurons in transgenic animals (figure 3b). In 1 mm brain slices with genetically expressed GFP, when cleared by passive CLARITY, tissue transparency reaches a plateau after 5 days, while the fraction of GFP remaining in the tissue decreases rapidly during clearing (Magliaro et al, 2016), demonstrating a trade-o↔ between transparency and protein retention. Antigens and fluorescent proteins are lost during tissue clearing.…”
Section: Loss Of Fluorescent Proteins and Antigensmentioning
confidence: 98%
“…Quantifying vessel staining using automated segmentation reduces the workload, especially compared to using tools like Fiji (Pan et al, 2016) or measuring fluorescent residue in clearing solution (Magliaro et al, 2016;Ke et al, 2013). Using the deep learning segmentation tool (Intellesis from Zeiss) we achieved reliable data collection with a further reduction in workload.…”
Section: Automated Image Segmentationmentioning
confidence: 99%